2018
DOI: 10.1186/s41100-018-0153-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of prognostic model for fistula maturation in patients with advanced renal failure

Abstract: Background: This study aimed to explore the role of patient's characteristic and haematological factors as predictive on the maturation of arteriovenous fistulae in patients who underwent vascular access surgery at the Royal Infirmary of Edinburgh. Methods: Retrospective data from 300 patients who had undergone fistula creation between February 2007 and October 2010 was examined. A predictive logistic regression model was developed using the backward stepwise procedure. Model performance, discrimination and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
2
1
1
Order By: Relevance
“…This is in accordance with data from USDRS in 2021 20 and the 2018 Indonesia Renal Registry report. 3 However, we found no relationship between sex and brachiocephalic AVF maturation consistent with studies by Won et al and Joannides et al 2 , 20 , 21 , 22 We also found no relationship between age and level of brachiocephalic AVF maturation consistent with studies by Chan et al and Siddiqui et al 1 , 2 , 5 , 23 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in accordance with data from USDRS in 2021 20 and the 2018 Indonesia Renal Registry report. 3 However, we found no relationship between sex and brachiocephalic AVF maturation consistent with studies by Won et al and Joannides et al 2 , 20 , 21 , 22 We also found no relationship between age and level of brachiocephalic AVF maturation consistent with studies by Chan et al and Siddiqui et al 1 , 2 , 5 , 23 …”
Section: Discussionsupporting
confidence: 90%
“…This is in accordance with data from USDRS in 2021 20 and the 2018 Indonesia Renal Registry report. 3 However, we found no relationship between sex and brachiocephalic AVF maturation consistent with studies by Won et al and Joannides et al 2,20,21,22 We also found no relationship between age and level of brachiocephalic AVF maturation consistent with studies by Chan et al and Siddiqui et al 1,2,5,23 Smoking is one of the factors that have an association with the incidence of atherosclerosis in arterial blood vessels. The quality of blood vessels can determine the maturation and patency rate of an AVF.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the USA, over 20 million adults were reported as suffering from this disease. In the UK, the prevalence of stage 3 to 5 CKD had touched 1.7 million adults, with the annual stage 5 CKD prevalence reaching 100 per one million in population (2). Based on the Indonesian Renal Registry (IRR)'s 2018 data, there were 66 433 new patients with CKD in Indonesia (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%